Problems, principles and prospects of international legal regulation of activities of private military and security companies - A. G. Volevodz (Vestnik MGIMO-Universiteta)
Современная обстановка, характеризующаяся процессами либерализации, глобализации, сокращения военных потенциалов, привела к быстрому увеличению числа частных военных и охранных предприятий (ЧВОП). В связи с этим возник вопрос о законности их деятельности с точки зрения международного права. В статье рассматриваются текущее состояние и перспективы международно-правового регулирования индустрии ЧВОП, роли и месте России в его формировании. The current situation, which can be characterized by the processes of liberalization, globalization and reduction of defense budgets, resulted in a rapid growth of the number of private military and security companies (PMSС). In this connection, a question arose of legitimacy of their activities from the point of view of international law. The article considers the current status and the prospects of international legal regulation of the PMSC sector and, the role and place of Russia in its formation.